1985
DOI: 10.1002/star.19850370105
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Benzylation of Potato Starch

Abstract: The formation of benzyl ethers of potato starch by etherification with benzyl chloride is base catalyzed and is therefore carried out at high pH. In a suspension of starch granules the rate of starch ether formation is found not to be linearly related to the concentration of hydroxyl ions in the water phase of the suspension. At the same pH widely different rates of reaction can be observed, to be due to the tendency of the starch granules to “absorb” hydroxyl ions when electrolytes are added to the suspension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…When NaOH content was above 8 %, stirring of the aqueous starch dispersion became difficult because of the viscosity increase. Free and coworkers reported that alkali consumption by starch and benzyl chloride was the most important factor in the benzylation of potato starch [13].…”
Section: Effect Of Alkali On Reaction Yieldmentioning
confidence: 99%
“…When NaOH content was above 8 %, stirring of the aqueous starch dispersion became difficult because of the viscosity increase. Free and coworkers reported that alkali consumption by starch and benzyl chloride was the most important factor in the benzylation of potato starch [13].…”
Section: Effect Of Alkali On Reaction Yieldmentioning
confidence: 99%
“…Starch ethers show a greater stability at higher pH. In addition, benzylation gives the modified starch a hydrophobic character that enables solubility in organic solvents and also endowed compatibility with synthetic petroleum plastics 2, 3. Because of the high hydrophobicity, the substituted starch shows low water solubility and almost no pasting viscosity 4.…”
Section: Introductionmentioning
confidence: 99%
“…The substitution reactions are often carried out in a water alkali medium containing benzyl chloride under heterogeneous conditions for lower temperatures up to 60°C 1, 3, 7, 14 and only to low degrees of substitution in the range from 0.1 to 1.0, where the requirements of crystallinity, ductility, stability, solution properties, and compatibility with other polymers are usually sufficient 10.…”
Section: Introductionmentioning
confidence: 99%